External auditory canal: Inferior, posterior-inferior, and anterior canal wall overhangs. (June 2018) - Dedhia, Kavita; Yellon, Robert F.; Branstetter, Barton F.; Best, Mark
Abstract: Objectives: To characterize anatomic variants of the external ear canal (EAC), specifically canal wall overhangs. EAC overhangs are problematic since they obstruct the view of the tympanic membrane (TM) and middle ear, possibly creating diagnostic and surgical difficulties. Methods: We reviewed pre-operative temporal bone CTs from children with cholesteatoma, and no history of EAC erosion or surgery. We measured the anterior canal wall overhang (ACOH), inferior (ICOH), and posterior-inferior (PICOH). A smaller angle means more EAC overhang. Angles >180° counted as 180° since they are non-obstructing. Analysis was performed between angular measurements and clinical and demographic data. Results: 86 patients (88 ears total) were studied. Mean age was 8.3 years. Only obstructing angles were analyzed statistically (<180°). The ICOH was most severe and occurred in 72/88 (81.8%) ears with a mean of 145.9 ± 12.8SD° (range 102–171°). ACOH occurred in 60/88 (68.2%) ears with a mean of 148.3 ± 10.9SD° (range 120–169°). PICOH occurred in 59/88 (67%) ears with a mean of 150.4 ± 9.2SD° (range 124–169°). Overall, ICOH was significantly more severe than PICOH (P = 0.026). ICOH had more Severe (142-102°) overhangs (27/88, 30.7%) than ACOH (17/88, 19.3%) or PICOH (11/88, 12.5%), but these were not significantly different. Analysis of clinical data showed that as the ICOH overhang became more severe, there was a history of significantly more (p = 0.039, r = −0.209) tympanostomy tubes placed. Conclusions: The greatest prevalence and severity of EAC overhang was the ICOH with a mean angle of 145.9°, compared with 148.3° and 150.4° for the ACOH and PICOH, respectively. This anatomic study demonstrates that ICOH and PICOH are prevalent anatomic variants and may possibly cause similar difficulties in otoscopic diagnosis and surgical TM and middle ear exposure as the well-known ACOH.